Comparison of solid phase extraction methods for the measurement of humic-like substances (HULIS) in atmospheric particles. (15th March 2020) - Zou, Chunlin; Li, Meiju; Cao, Tao; Zhu, Mengbo; Fan, Xingjun; Peng, Shiyun; Song, Jianzhong; Jiang, Bin; Jia, Wanglu; Yu, Chiling; Song, Haiyan; Yu, Zhiqiang; et al.
Abstract: Humic-like substances (HULIS) constitute a significant fraction of the water-soluble organic compounds in the environment and influence many properties of atmospheric aerosols. In this study, three solid phase extraction (SPE) methods that involve the use of hydrophilic/lipophilic balanced (HLB) resin with pure methanol (HLB-M), HLB resin with 2% (v/v) ammonia/methanol (HLB-N), and Bond Elut PPL (Priority PolLutant) resin with methanol (PPL), were compared for the isolation of HULIS from atmospheric aerosols. The HLB-N and PPL methods efficiently recovered Suwannee River fulvic acid (SRFA) and were excellent for quantifying HULIS at low levels in aerosols. All three SPE methods were favorable for the elution of aromatic and strongly UV-absorbing compounds. However, the chemical structures and molecular compositions of the HULIS isolated by the three methods showed some differences. The HULISHLB-N and HULISPPL fractions contained higher concentrations of aliphatic and aromatic C–H groups than did the HULISHLB-M fraction, indicating that relative higher content of weak polar organic species in HULIS fractions isolated by the HLB-N and PPL methods than those isolated by the HLB-M method. Moreover, the HULISHLB-N and HULISPPL were both characterized by having lower relative abundance-weighted modified aromaticity index values and higher concentrations of S-containing compounds than the HULISHLB-M, as indicated by Fourier transform ion cyclotron resonance mass spectrometry. Some N-containing structures were identified only in the HULISHLB-N, suggesting that some of HULIS molecules were changed during the HLB-N treatment. Based on these comparisons of the three methods, we found that the PPL method serves equally good as compared to other two methods, and therefore, one can utilize PPL method also for HULIS isolation and characterization. Highlights: HLB-M, HLB-N, and PPL methods are comparatively investigated and estimated. All SPE methods were favorable for high UV absorbance and aromatic compounds. Some HULIS molecules were changed during the HLB-N treatment. The PPL method serves equally good for HULIS isolation and characterization.